Hadis Tentang Anjuran Waktu Mandi Yang Sunnah Dalam Kitab Musnad Ahmad Bin Hanbal dan Pembuktian Sains - Harahap, Abdul Rahman (UIN Sumatera Utara Medan, 2024)
The Prophet Muhammad (PBUH) is known for his constant attention to personal and environmental cleanliness, with one of his Sunnahs being to bathe before the Friday prayer (Shalat Jumaat). This practice is not only an act of worship but also offers health benefits. This study aims to explore the scientific benefits of the recommendation to bathe before the Friday prayer. The research method used is qualitative with a literature study approach, examining hadiths in the Musnad of Ahmad ibn Hanbal. The findings indicate that the hadith recommending bathing before the Friday prayer is authentic based on the takhrij hadith conducted. This hadith has numerous chains of narration supporting its validity as a hujjah (evidence). Scientifically, bathing provides significant benefits for the body, both in terms of physical and emotional health. Bathing before the Friday prayer, particularly with warm water at around 30-40°C, is advised to align with midday temperatures. This corresponds with practices in typically hot desert regions, showing that the recommendation to bathe before the Friday prayer is based not only on religious aspects but also on strong scientific grounds. This study concludes that the recommendation to bathe before the Friday prayer in the hadith has relevance from both health and religious perspectives, making it practicable according to prevailing conditions.